“Plant Performance Operations and Financial Tracking (PROFIT)” Mobile Application as Integrative Strategic Information Systems in Pertamina - Daniswara Krisna Prabatha; Seger Handoyo (Universitas Sebelas Maret, 2022)
Plant Performance Operations and Financial Tracking (PROFIT) mobile application is an effort by Pertamina, an Indonesian State-owned Enterprise that runs an integrated core business at oil, gas, and renewable energy, to implement an integrative strategic information system (SIS). PROFIT aims to provide information among employees, to monitor the performances of the refinery, facilitate communication and coordination of work activities among employees, and support the budgeting process at several projects initiated. This study examines the effect of the PROFIT mobile application as an integrated information system on employee performance. The results show that PROFIT Apps as SIS, is a positive and significant variable in the performance of the Process Engineering of Pertamina Refinery Unit III Plaju’s Employees. The samples used in the study were Process Engineering of Pertamina Refinery Unit III Plaju’s Employees. Data collection methods use questionnaires and data processing techniques used through multiple linear regression analysis. This research could contribute ideas and scientific study materials for PT. Pertamina (Persero) Refinery Unit III and other company management in setting policies related to development of SIS as integrative information systems as an effort to influence corporate strategy and performance positively.Keywords: corporate performance; mobile application; refinery performance; strategic information systems